Penerapan Pembiasaan “Tadarus Sebelum Belajar” dalam Membentuk Karakter Religius Siswa di SMP Negeri 7 Kota Serang - Nabila Ayu Lestari; Syaima Fikya Nabilah; Rita Safira; Neng Lilis; Siti Hardiyanti; Fiska Sulistyo Rani; Novita Kurniastuti; Rikza Fauzan (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to determine the Role of Tadarus Al-Qur'an as one form of Religious Education that can be given to Students in the midst of this Era of Moral Degradation, especially to form Students' Religious Character through the Habit of Tadarus Before Studying held at SMP Negeri 7 Serang City. The research method used in this study is literature review. In this literature review method, it is carried out by systematically searching the Google Scholar database by selecting several journals as a literature review while the direct observation technique is carried out by the Research Team who are carrying out the Introduction to the School Field (PLP) FKIP Untirta within a period of 2 (two) months by monitoring the Activities or Activities that occur at School. The results of this study are that the Habit of Tadarus Before Studying which was carried out for 35 Minutes at SMP Negeri 7 Serang City has a positive impact, especially in forming the Religious Character of Students which has been proven by their Personality in carrying out daily Activities based on Religious Values. Of course, there is the involvement of Homeroom Teachers, BK Teachers and Parents as Assistants in making children accustomed and accustomed to Habitual Activities that refer to Religious Education.